2015
DOI: 10.5941/myco.2015.43.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl Eburicoic Acid from Laetiporus sulphureus var. miniatus Suppresses Inflammation in Murine Macrophage RAW 264.7 Cells

Abstract: The basidiomycete Laetiporus sulphureus var. miniatus belongs to the Aphyllophorales, Polyporaceae, and grows on the needleleaf tree. The fruiting bodies of Laetiporus species are known to produce N-methylated tyramine derivatives, polysaccharides, and various lanostane triterpenoids. As part of our ongoing effort to discover biologically active compounds from wood-rotting fungi, an anti-inflammatory triterpene, LSM-H7, has been isolated from the fruiting body of L. sulphureus var. miniatus and identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The relative invasion activity of MMP-2/9 mRNA were analyzed the band intensity using a Whereas, the hexane and chloroform fractions of L. miniatus were inhibited by 50%, MMP-2 and MMP-9 activations compared to the thrombin only treated group. This finding may lend further support to previous studies [20,23], where acetyl eburicoic acid derived from the fruiting bodies of L. miniatus demonstrated potent anti-cancer effects on HL-60 human myeloid leukemia cells, resulting from apoptosis activation. Therefore, we suggest that the hexane and chloroform fractions of L. miniatus might serve as potential antiinvasive agents in oral cancer, although further experiments will need to be carried out in order to identify the active compounds present within the hexane and chloroform fractions of L. miniatus.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The relative invasion activity of MMP-2/9 mRNA were analyzed the band intensity using a Whereas, the hexane and chloroform fractions of L. miniatus were inhibited by 50%, MMP-2 and MMP-9 activations compared to the thrombin only treated group. This finding may lend further support to previous studies [20,23], where acetyl eburicoic acid derived from the fruiting bodies of L. miniatus demonstrated potent anti-cancer effects on HL-60 human myeloid leukemia cells, resulting from apoptosis activation. Therefore, we suggest that the hexane and chloroform fractions of L. miniatus might serve as potential antiinvasive agents in oral cancer, although further experiments will need to be carried out in order to identify the active compounds present within the hexane and chloroform fractions of L. miniatus.…”
Section: Resultssupporting
confidence: 77%
“…Previous studies have reported various compounds derived from L. miniatus, which include polysaccharides, benzofuran glycoside, acetylenic acid, lanostanoid triterpene and β-1,3-1,4-glucanase [16][17][18][19]. Other investigations have shown that extracts and specific fractions obtained from L. miniatus have various positive biological and pharmacological activities, including anti-tumor [20][21][22], anti-inflammatory [23,24], anti-microbial, and anti-fungal activities. Some of these properties observed were seen with the hexane fraction isolated from L. miniatus lipid extracts [25]; while, specifically, anti-oxidant activities were seen with its hot water soluble and hot alkali soluble polysaccharides [26].…”
Section: Introductionmentioning
confidence: 99%
“…Till date, treatments are not able to solve these disorders suggesting finding of new antiinflammatory therapeutic compounds. 65 To discover biologically active antiinflammatory compounds from wood rotting fungi, Saba et al (2015) have isolated a triterpene, LSM-H7, from fruiting bodies of L. sulphureus var. miniatus inhabiting in Mt.…”
Section: Anti-inflammationmentioning
confidence: 99%
“…Jayasooriya et al (2011) reported that exopolysaccharides purified from the LS culture medium significantly decreased NO production of LPSinduced BV2 microglia cells at a dosage of 2.0 mg/ mL; no cytotoxicity was observed. Saba et al (2015) and Wang et al (2017a) both applied triterpenes purified from LS to RAW 264.7 cells and reported an improvement in the viability and NO production at dosages of 25-100 µg/mL and 0.02-0.08 µM, respectively. These studies confirmed that they were able to attenuate the excessive immune activation of the selected cells without causing cytotoxicity within the chosen dosage range.…”
Section: Discussionmentioning
confidence: 99%
“…LS-derived triterpene eburicoic acid has been described by Wang et al (2017a) as able to inhibit LPS-induced activation of NFkB pathways and downregulate the inflammatory response in RAW 264.7 cells. Saba et al (2015) also reported that acetyl eburicoic acid from LS can reduce the pro-inflammatory cytokines secreted by LPS-induced RAW 264.7 cells. Ergosterol is a fungal sterol, known as pro-vitamin D2, which inhibits NFkB expression in RAW 264.7 cells and exerts an anti-inflammatory effect (Ma et al, 2013).…”
Section: A B C Dmentioning
confidence: 92%